The NHLBI SMARTT Program: A Novel Approach to Facilitate Translational Research for Heart, Lung and Blood Diseases. Issue 12 (10th June 2016) - Ebert, Ray F.; Danthi, Narasimhan S.; Charette, Marc F.; Hanspal, Manjit; Mondoro, Traci H.; Noel, Patricia J.; Olive, Michelle; Punturieri, Antonello; Moore, Timothy M.
Abstract : Supplemental Digital Content is available in the text.